2017
DOI: 10.3892/ol.2017.7474
|View full text |Cite
|
Sign up to set email alerts
|

Regulator of G‑protein signaling 5 enhances portal vein invasion in hepatocellular carcinoma

Abstract: Abstract. Portal vein invasion (PVI) is a major prognostic factor in hepatocellular carcinoma (HCC). The aim of the present study was to identify molecules that regulate PVI. Sections of cancerous tissue, paired noncancerous tissue and the PVI area were collected from 3 frozen HCC sections, using laser microdissection. The present study focused on 3 upregulated molecules, integrin β3 (ITGB3), secreted phosphoprotein 1 (SPP1) and regulator of G-protein signaling 5 (RGS5), and 2 molecules that were downregulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…In this study, we found that RGS5 appears to be involved in the aggressive biological features of OSCC, which can be mediated by properties (Huang et al, 2012;Wang et al, 2010). In contrast, high RGS5 expression in HCC was reported to be associated with various aggressive properties, such as vascular invasion, intrahepatic metastasis, and EMT (Hu et al, 2013;Umeno et al, 2018). These reports indicate that the role of RGS5 in carcinoma is organ specific.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…In this study, we found that RGS5 appears to be involved in the aggressive biological features of OSCC, which can be mediated by properties (Huang et al, 2012;Wang et al, 2010). In contrast, high RGS5 expression in HCC was reported to be associated with various aggressive properties, such as vascular invasion, intrahepatic metastasis, and EMT (Hu et al, 2013;Umeno et al, 2018). These reports indicate that the role of RGS5 in carcinoma is organ specific.…”
Section: Discussionmentioning
confidence: 69%
“…Hu et al (2013) reported that regulator of G-protein signaling (RGS) 5 is related with tumor invasion by inducing EMT of hepatocellular carcinoma (HCC) cells. We also demonstrated that RGS5 expression is closely related with portal vein invasion and intrahepatic metastasis in HCC (Umeno et al, 2018). The RGS family is a group of multifunctional proteins that regulate cellular signaling events downstream of G-protein coupled receptors (Hurst & Hooks, 2009).…”
mentioning
confidence: 66%
See 3 more Smart Citations